Percepção ambiental dos usuários da avenida Beira Rio na cidade de Itumbiara GO - Rodrigues, Vercilene de Paula (2014)
The city of Itumbiara, Goiás, has a history marked by the Paranaíba River in all of its achievements and accomplishments. The city s growth was spurred by this river, from the time when rafts brought food, medicine or any other material the city s commerce and population needed. In light of the river s historic and economic importance for Itumbiara, the goal of this research study is to evaluate how its citizens perceive the Beira Rio Avenue from an environmental point of view. This avenue was built on the right bank of the Paranaíba River, inside the city s urban perimeter. To accomplish that, the study analyzed bibliographical references, surveyed historical documents about Itumbiara and conducted interviews with its citizens. The results demonstrate that its citizens are concerned about the river s pollution, the trash scattered along the avenue and the lack of trees. Nevertheless, they are pleased with the scenic beauty of the location, the expansion of entertainment options in the city and the availability of locations for them to do physical exercises. The citizens of Itumbiara have a very positive outlook regarding the Beira Rio Avenue; however, they are clear about their dissatisfaction with the lack of public investments targeting safety, infrastructure for physical activities and environmental education projects for citizens.